Fungal Mastoiditis in AIDS Patients: Reported Cases - Carenzi, Lucas Rodrigues; Silveira, Flavia; Faidiga, Gabriel Bijos; do Lago, Tassiana; Yassuda, Camila Carrara; Massuda, Eduardo Tanaka; Hyppolito, Miguel Angelo (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Fungal mastoidits by Aspergillus fumigates predominantly occurs in immunosuppressed patients. Diagnosis is usually hard and disease is potentially fatal. Treatment is comprised of antifungal therapy, surgical debridement and immunosuppression correction.Case Report: This article reports a case of fungal mastoiditis in a patient with acquired immunodeficiency syndrome (AIDS). The treatment performed was that of surgery associated with antifungal therapy. The patient's facial nerve was not affected, what does not exclude potentially fatal complications of mastoiditis.
Keywords: acquired immunodeficiency syndrome; mastoiditis; Aspergillus fumigatus